Influence of Farm Size on Selected Milk Quality and Hygiene Traits in Romanian Spotted Cows - Ligia Berzava; Alin Bucur (Prisecaru); Bogdan-Roberto Mihuța; Ludovic Toma Cziszter; Silvia Erina (Scientific Papers Animal Science and Biotechnologies, 2023)
Researches were carried out on 1707 Romanian Spotted cows raised in farms from Hunedoara County that were under the official performance control scheme. According to the number of milking cows (farm size), farms were divided into three categories small (n≤10 cows), middle (n=11 to 25 cows) and large (n>25 cows). The influence of the farm size on the milk dry matter percentage, milk pH, urea content in milk, and milk somatic cell count was determined by using ANOVA, and lactation curve for these traits was drawn using the gamma incomplete function. Generally, the farm size had a significant influence on all studied milk traits (p<0.01). Dry matter percentage in milk varied from 11.6% in middle farms to 12.6% in large farms. The highest value for pH was found, on average, in small farms (6.61), while the lowest value was in large farms (6.57). Urea content of the milk Had higher values in middle farms (32.4 to 33.1 mg/100g), followed by small farms (29.5 to 32.5 mg/100g) and the lowest values were observed in large farms (28.0 to 295 mg/100g). Somatic cell count was, on average, higher in middle farms (652.33x1000), while the lowest value was observed in small farms (440.54x1000).